Seasonal adjustment of the Spanish sales daily data - Ángel Cuevas; Ramiro Ledo; Enrique M. Quilis (SERIEs - Journal of the Spanish Economic Association, 2021)
We present a procedure to perform seasonal adjustment over daily sales data. The model adjusts daily information from the Immediate Supply of Information System for Value Added Tax declaration forms compiled by the Spanish Tax Agency. The procedure performs signal extraction and forecasting at the daily frequency, by means of an unobserved components model. The daily information allows a permanently updated monitoring of the short-term economic conditions of the Spanish economy.
Keywords: C22; C32; C53; 330; Tax data; Daily time series; Short-term forecasts; Unobservedcomponents model